2012
DOI: 10.1111/j.1471-6712.2012.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, psychosocial, somatic and treatment factors predicting return to work after breast cancer treatment

Abstract: Chemotherapy is associated with longer periods of sick leave. Cognitive functions do not predict RTW. Independently of any adjuvant therapy, most women eventually RTW in a few months. The ability to predict RTW after BC treatment should help prepare higher-risk patients for delayed RTW and allow earlier interventions to restore their social relations and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 27 publications
(40 reference statements)
5
34
1
1
Order By: Relevance
“…Moreover, we did not detect any link between emotional functioning and RTW, thus confirming the results of Hedayati et al. . We hypothesised that high levels of physical functioning, role functioning and social functioning would drive RTW, but we did not find any evidence for this.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Moreover, we did not detect any link between emotional functioning and RTW, thus confirming the results of Hedayati et al. . We hypothesised that high levels of physical functioning, role functioning and social functioning would drive RTW, but we did not find any evidence for this.…”
Section: Discussionsupporting
confidence: 89%
“…In contradiction of the results of Hedayati et al. , cognitive functioning has been identified as a RTW determinant for cancer survivors. An integrative review concluded that cognitive impairments had a deleterious effect on work‐related outcomes such as RTW .…”
Section: Introductioncontrasting
confidence: 72%
See 3 more Smart Citations